2014
DOI: 10.1007/s00213-014-3715-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixing alcohol with energy drink on objective and subjective intoxication: results from a Dutch on-premise study

Abstract: BackgroundThe purpose of this on-premise study was to determine if alcohol mixed with energy drink (AMED) consumption masks the subjective feelings of intoxication when compared to consuming alcohol only.MethodsThe study was conducted on five nights in the city center of Utrecht. N = 997 people leaving bars were interviewed about their alcohol consumption with and without energy drinks, for that particular evening and for other occasions. People reporting drug and medication use were excluded (N = 84). Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 34 publications
5
28
1
Order By: Relevance
“…Contrary to what may be expected given the association between caffeine and alcohol use and increased alcohol consumption (e.g., O’Brien et al 2008; Pennay et al 2015; Thombs et al 2010; Thombs et al 2011; Verster et al 2015) or increased desire for alcohol (Heinz et al 2013; Marczinski et al 2013; Marczinski et al 2016; McKetin and Coen, 2014), in the present study, added caffeine did not affect the number of self-administered drinks. There may be several explanations for this result.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what may be expected given the association between caffeine and alcohol use and increased alcohol consumption (e.g., O’Brien et al 2008; Pennay et al 2015; Thombs et al 2010; Thombs et al 2011; Verster et al 2015) or increased desire for alcohol (Heinz et al 2013; Marczinski et al 2013; Marczinski et al 2016; McKetin and Coen, 2014), in the present study, added caffeine did not affect the number of self-administered drinks. There may be several explanations for this result.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, field research has linked co-consumption of caffeine and alcohol with increased breath alcohol concentration or a greater number of alcohol drinks consumed (Pennay et al 2015; Thombs et al 2010; Thombs et al 2011; Verster et al 2015). Animal research also suggests that some caffeine doses are associated with increased alcohol consumption (Dietze and Kulkosky 1991; Kunin et al.…”
Section: Introductionmentioning
confidence: 99%
“…When including the three omitted studies (Penning et al , Lubman et al , Verster et al ) no relevant changes were seen in the overall outcome of the meta‐analyses. Again, the meta‐analysis of between‐group comparisons revealed that AMED consumers on a typical drinking occasion consume significantly more alcohol than AO consumers ( p = 0.0001, ES = 0.453, 95%CI = 0.289 to 0.617).…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, due to ethical constraints, achieved BAC levels in controlled studies usually do not reach BAC levels seen in nightlife [6]. In this context, a recent study with a naturalistic design (i.e., participants alcohol consumption is not influenced by the researchers) revealed an estimated peak BAC of 0.18% [7].…”
Section: Introductionmentioning
confidence: 99%